Full Step Cycle Kinematic and Kinetic Comparison of Barefoot Walking and a Traditional Shoe Walking in Healthy Youth: Insights for Barefoot Technology - Yi Xu; Qinghua Hou; Chuhuai Wang; Andrew J. Sellers; Travis Simpson; Bradford C. Bennett; Shawn D. Russell (Applied Bionics and Biomechanics)
Objective. Barefoot technology shoes are becoming increasingly popular, yet modifications are still needed. The present study aims to gain valuable insights by comparing barefoot walking to neutral shoe walking in a healthy youth population. Methods. 28 healthy university students (22 females and 6 males) were recruited to walk on a 10-meter walkway both barefoot and in neutral running shoes at their comfortable walking speed. Full step cycle kinematic and kinetic data were collected using an 8-camera motion capture system. Results. In the early stance phase, the knee extension moment (MK1), the first peak absorbed joint power at the knee joint (PK1), and the flexion angle of knee/dorsiflexion angle of the ankle were significantly reduced when walking in neutral running shoes. However, in the late stance, barefoot walking resulted in decreased hip joint flexion moment (MH2), second peak extension knee moment (MK3), hip flexors absorbed power (PH2), hip flexors generated power (PH3), second peak absorbed power by knee flexors (PK2), and second peak anterior-posterior component of joint force at the hip (APFH2), knee (APFK2), and ankle (APFA2). Conclusions. These results indicate that it should be cautious to discard conventional elements from future running shoe designs and rush to embrace the barefoot technology fashion.